Munchausen by proxy syndrome mimicking systemic autoinflammatory disease: case report and review of the literature - Helmut Wittkowski (Pediatric Rheumatology Online Journal, 2017)
Abstract Background Systemic autoinflammatory diseases (SAIDs) represent a growing number of monogenic, polygenic or multifactorial disorders that are often difficult to diagnose. Case presentation Here we report a patient who was initially erroneously diagnosed and treated for SAID. Symptoms consisted of recurrent fever, erythematous and/or blistering skin lesions, angioedema, susceptibility to bleeding, external ear infections and reversible anisocoria in the absence of laboratory evidence of systemic inflammation. After two and a half years of extensive diagnostic work-up and multiple empirical therapies, a final diagnosis of Munchausen by proxy syndrome (MBPS) was established. Conclusions The diagnosis of SAID needs to be carefully reassessed if measurable systemic inflammation is missing, and MBPS should be included in the differential diagnosis.